Advances in cellular and molecular pathways of salivary gland damage in Sjögren’s syndrome - Qi, Wenxia; Tian, Jiexiang; Wang, Gang; Yan, Yanfeng; Wang, Tao; Wei, Yong; Wang, Zhandong; Zhang, Guohua; Zhang, Yuanyuan; Wang, Jia (Frontiers in Immunology, 2024)
Sjögren’s Syndrome (SS) is an autoimmune disorder characterized by dysfunction of exocrine glands. Primarily affected are the salivary glands, which exhibit the most frequent pathological changes. The pathogenesis involves susceptibility genes, non-genetic factors such as infections, immune cells-including T and B cells, macrophage, dendritic cells, and salivary gland epithelial cells. Inflammatory mediators such as autoantibodies, cytokines, and chemokines also play a critical role. Key signaling pathways activated include IFN, TLR, BAFF/BAFF-R, PI3K/Akt/mTOR, among others. Comprehensive understanding of these mechanisms is crucial for developing targeted therapeutic interventions. Thus, this study explores the cellular and molecular mechanisms underlying SS-related salivary gland damage, aiming to propose novel targeted therapeutic approaches.